Killer-Cell Immunoglobulin-Like Receptors (KIR) in HIV-Exposed Infants in Cameroon - Kagoué Simeni Luc-Aimé; Yindom Louis-Marie; Loni Ekali Gabriel; Clauvis Kunkeng Yengo; F. Esemu Livo; Nguedia Jules Clement Assob (Journal of Immunology Research)
The biological reason(s) behind persistent mother-to-child transmission (MTCT) of HIV (albeit at reduced rate compared to the preantiretroviral therapy era) in spite of the successful implementation of advanced control measures in many African countries remains a priority concern to many HIV/AIDS control programs. This may be partly due to differences in host immunogenetic factors in highly polymorphic regions of the human genome such as those encoding the killer-cell immunoglobulin-like receptor (KIR) molecules which modulate the activities of natural killer cells. The primary aim of this study was to determine the variants of KIR genes that may have a role to play in MTCT in a cohort of infants born to HIV-infected mothers in Yaoundé, Cameroon. We designed a cross-sectional study to molecularly determine the frequencies of 15 KIR genes in 14 HIV-exposed infected (HEI), 39 HIV-exposed/uninfected (HEU), and 27 HIV-unexposed/uninfected (HUU) infants using the sequence specific primer polymerase chain reaction (PCR-SSP) method. We found that all 15 KIR genes were present in our cohort. The frequency of KIR2DL1 was significantly higher in the unexposed (control) group than in the HIV-exposed group (OR=0.22, P=0.006). Stratifying analysis by infection status but focusing only on exposed infants revealed that KIR2DL5, KIR2DS1, and KIR2DS5 were significantly overrepresented among the HIV-exposed/uninfected compared to infected infants (OR=0.20, P=0.006). Similarly, the frequencies of KIR2DS1, KIR2DS5, and KIR2DL5 were significantly different between infants perinatally infected with HIV (HIV+ by 6 months of age) and HIV-negative infants. Our study demonstrates that KIR genes may have differential effects with regard to MTCT of HIV-1.